2020
DOI: 10.48550/arxiv.2007.12424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural Strategic Abilities in Voting Protocols

Abstract: Security properties are often focused on the technological side of the system. One implicitly assumes that the users will behave in the right way to preserve the property at hand. In real life, this cannot be taken for granted. In particular, security mechanisms that are difficult and costly to use are often ignored by the users, and do not really defend the system against possible attacks. Here, we propose a graded notion of security based on the complexity of the user's strategic behavior. More precisely, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A good example of a specific domain is formal verification of voting procedures and elections, with a number of classical requirements, such as election integrity, ballot secrecy, receipt-freeness, and voter-verifiability [42,44]. Some recent case studies [23,25,28] have shown that practical verification of such scenarios is still outside of reach. Some tools do not support intuitive specification and validation of models; some others have limited property specification languages.…”
Section: Application Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…A good example of a specific domain is formal verification of voting procedures and elections, with a number of classical requirements, such as election integrity, ballot secrecy, receipt-freeness, and voter-verifiability [42,44]. Some recent case studies [23,25,28] have shown that practical verification of such scenarios is still outside of reach. Some tools do not support intuitive specification and validation of models; some others have limited property specification languages.…”
Section: Application Domainmentioning
confidence: 99%
“…Unfortunately, model checking of agents with imperfect information is ∆ P 2 -to PSPACE-complete for memoryless strategies [9,22,43] and EXPTIME-complete to undecidable for agents with perfect recall [18,20]; also, the problem does not admit simple incremental solutions [10,16,17]. This has been confirmed in experiments [11,12,21,26,40] and case studies [23,25,28].…”
Section: Introductionmentioning
confidence: 97%